Excavations at Can Hasan. First Preliminary Report, 1961 - French, D. H.
The Site – The 1961 Season – The Plan of the First Campaign – Architecture – Finds – Small Objects – Stratigraphy and Chronology – Catalogue of Illustrated Pottery.